2018
DOI: 10.1002/mgg3.479
|View full text |Cite
|
Sign up to set email alerts
|

A novel large germ line deletion in adenomatous polyposis coli (APC) gene associated with familial adenomatous polyposis

Abstract: BackgroundFamilial adenomatous polyposis (FAP) is a familial colorectal cancer predisposition syndrome characterized by the development of numerous colorectal polyps, which is inherited in an autosomal dominant manner. FAP is caused by germ line mutations in adenomatous polyposis coli (APC) gene. Here, we described the identification of a causative APC gene deletion associated with FAP in an Iranian family.MethodsDiagnosis of FAP was based on clinical findings, family history, and medical records (colonoscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It has been shown that the location of germline mutations in the APC gene is the most striking source of variability affecting the number of polyps that will develop in the colon of FAP patients 13 , 41 , 42 . In accordance, the current study found a correlation between the severity of the disease in FAP patients who donated their affected embryos for our FAP-hESC lines and the 3D structure of their derived colon organoids and the location of their germline APC mutations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the location of germline mutations in the APC gene is the most striking source of variability affecting the number of polyps that will develop in the colon of FAP patients 13 , 41 , 42 . In accordance, the current study found a correlation between the severity of the disease in FAP patients who donated their affected embryos for our FAP-hESC lines and the 3D structure of their derived colon organoids and the location of their germline APC mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The overall frequency of the APC gene mutation in sporadic colorectal cancer is about 25-30%, but some reports from Iran have revealed a different mutation profile [23][24][25][26] . This may be because of geneenvironmental interaction factors and predominantly because of the heterogeneous nature of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…According to the GLOBOCAN 2018 statistics, CRC is the third most commonly diagnosed malignancy and the second cause of cancer‐related death globally 2 . Approximately 70‐80% of the cases are sporadic, and the rest of them are hereditary CRC 3,4 . In the recent decade, several different CRC screening methods including fecal occult blood test (FOBT), stool DNA test, sigmoidoscopy, CT colonography, colonoscopy, and double‐contrast barium enema have been developed 5 .…”
Section: Introductionmentioning
confidence: 99%